A comparative study of hBM‐MSCs' differentiation toward osteogenic lineage in the presence of progesterone and estrogen hormones separately and concurrently in vitro. (6th May 2020) - Soltanyzadeh, Maryam; Ghollasi, Marzieh; Halabian, Raheleh; Shams, Mehdi
Abstract: Promising cell sources for tissue engineering comprise bone marrow derived‐mesenchymal stem cells (BM‐MSCs) that have multiple differentiation potentials. Also, sex hormones act as important elements in bone development and maintenance, and the roles of two female sex steroid hormones known as estrogen (17‐β estradiol) and progesterone in osteogenic differentiation of human BM‐MSCs (hBM‐MSCs) are studied. For this purpose, hBM‐MSCs were treated with a 1 × 10 −6  M concentration of 17‐β estradiol and progesterone separately and simultaneously while the optimum concentrations were obtained by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay. Osteogenic differentiation tests including measurement of alkaline phosphatase (ALP) enzyme activity, the content of total mineral calcium, mineralized matrix staining by Alizarin Red and Von Kossa solutions, real‐time reverse transcription polymerase chain reaction (RT‐PCR), and immunofluorescence staining were carried out on Days 7 and 14 of differentiation. To exhibit the morphology of the cells, the BM‐MSCs were stained with acridine orange (AO) solution. In this study, the results of ALP activity assay, calcium content and real‐time RT‐PCR assay and also all tests of differentiation staining have shown that 17‐β estradiol has been recognized as an enhancing factor of osteogenic differentiation. Furthermore, MTT assay and AO staining revealed progesterone as a factor that seriously improved the proliferation of hBM‐MSCs. Generally, the 17‐β estradiol individually or in the presence of progesterone has more effects on BM‐MSCs' osteogenic differentiation compared to progesterone alone. In this study, it is indicated that the effect of the 17‐β estradiol and progesterone concurrently was the same as individual 17‐β estradiol on the differentiation of hBM‐MSCs. Abstract : The effect of famale sex steroid hormones on proliferation and differentiation of human bone morrow mesechymal stem cells.